Factors Influencing Sexual Harassment In The Malaysian Workplace - Ismail, Mohd Nazari; Lee , Kum Chee; Chan , Foong Bee (Asian Academy of Management (AAM), 2007)
This study examined the potential risks factors associated with sexually harassing behaviors within the framework of the four-factor model of sexual harassment. The factors examined are unprofessional work environment, skewed gender ratio in the workplace, knowledge of grievance procedure for sexual harassment, sexist attitudes among co-workers, privacy of workspace, physical attractiveness, dress manner of victims, job status, and sex roles. The dependent variable is incidence of sexual harassment which was evaluated using the Sexual Experience Questionnaire developed by Fitzgerald, Shullman, Bailey, Richards, Swecker, Gold, Ormerod, and Weitzman (1988). Data were collected from 657 women employees working in Malaysian organizations. The findings showed that the predictions of the four-factor model are also largely true in the case of the Malaysian workplace. The study also found that sexual harassment behaviors are fairly widespread in Malaysia